A política de formação continuada dos (das) professores (as) da educação do campo em Confresa-MT - Carneiro, Terezinha de Jesus Aires (2013)
This dissertation studies the teachers’ continuous training policy of Rural Education in Confresa, northeast of Mato Grosso, Araguaia region. The objective was to understand the continuous training policy, observing the rural specificity on the offered formative principles, regarding the organization of these proposals. The research is justified by the need of seeking subsidies referred to the teacher’s qualification in the historicity of the formations in itself and for the representation in a set of demanded educational actions for the teacher’s formation in the Rural Education. The reflections of this text focus on the theorical aspects of the elaboration and organization of these policies and offer the discussion of the historical characterization on how it has occurred in this location, particularly, from 2005 to 2010. The issue inquires about the teachers’ continuous training policy of Rural Education, formulated on the basis of the theorical and national normative assumptions, covers the State educational policy decisions, and lies on the proposition and exercise of continuous training activities in the municipal ambit, on how it’s going to be the rural teachers’ teaching. The study, from the policy cycles analysis, is inserted in a discussion about the State Power on the teachers’ continuous training policy and in the understanding about the subject provided by the teachers that take part in this training from schools. The theorical field has allowed the development of studies referenced in the rural education’s intellectuals, such as Arroyo (2005, 2007, 2012), Caldart (2005, 2004), Hage (2010), Molina (2003, 2009) e Reck (2007, 2010). It was still referenced in teacher’s training theorists as Imbernón (2010, 2011), Nóvoa (1992, 1999, 2004, 2009) e Tardif (1991, 2000, 2005, 2012). With regards to the theorical-methodological approach, it was made the option for the policy cycle of Ball (2006) understood as cyclical, in a movement between the influence context, text context and practice context. With this idea of the policy cycle, the methodology is characterized by the qualitative research, involving bibliographic study, documentary analysis and interviews made with teachers that participated in the continuous training policies. The study conducted highlights the conception of the continuous training in official documents, therefore, policy formation, aiming a teachers’ continuous formation in rural education, in search of updating and contextualization of the educational practices. These public educational policies are present in the school, or as the interviewed teachers say “on the school’s floor” and they maximize teaching practices, increase and move forward new conceptions on the role of the teacher, the conception of rural education, the conditions of peasant exercise of the rural students, as well as an specific organization process of the educational institutions and the suitability of the school contents for the educational practices to be more involving, unbound by reality where they live and the teaching knowledge that values the social rural area, and also, contributes with the socio- economic, educational and cultural development of the peasant population.